RESOLUTION OF DISPUTES IN APPLICATIONS FOR POSTPONEMENT OF DEBT PAYMENT OBLIGATIONS BY EMPLOYEES AGAINST COMPANIES FAILING TO FULFILL THEIR OBLIGATIONS (A Case Study of Decision Number: 20/Pdt.Sus-PKPU/2019/PN.Niaga.Mdn) - Aziz, Muhammad Fauzan; Sunarmi, Sunarmi; Siregar, Mahmul; Robert, Robert (Universitas Muhammadiyah Tangerang, 2024)
This research examines the use of Postponement of Debt Payment Obligations as an alternative mechanism for resolving disputes between employees and companies that fail to fulfill employees' normative rights. Using a normative legal research method and qualitative analysis, the study explores the legal framework for filing Postponement of Debt Payment Obligations, the dispute resolution process in the Commercial Court, and an analysis of Decision Number 20/Pdt.Sus-PKPU/2019/PN.Niaga.Mdn. The findings demonstrate that Law No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations provides a legal mechanism for employees to claim their rights. The Postponement of Debt Payment Obligations process includes debt verification, creditors' meetings, and reconciliation efforts. The analyzed decision highlights the effectiveness of Postponement of Debt Payment Obligations in resolving disputes, resulting in the full payment of employees' rights while giving companies an opportunity to fulfill their obligations. This suggests that Postponement of Debt Payment Obligations can serve as a fair and efficient solution for safeguarding employees' rights.Keywords: Dispute Resolution, Application for Postponement of Debt Payment Obligations, Employees, Companies